The determinants of foreign direct investment flows to the federal region of Kurdistan - Almas Heshmati; Rhona Davis (Institute for the Study of Labor (IZA), 2007)
The flow of foreign direct investment (FDI) has increased dramatically in the last two decades. However, the distribution of FDI is highly unequal and the competition among countries to attract foreign investors is fierce. This report investigates the determinants of FDI inflows to developing countries in general and to the Federal Region of Kurdistan (FRK) in particular. The emphasis is on the impact of the Kurdistan Regional Government (KRG) active policy measures to encourage inward FDI to the region and at the same time to discourage outward FDI, respectively. We explore whether factors that affect FDI to developing countries affect Kurdistan differently and estimate the magnitude of heterogeneity and its effect by location and level of their development. The current regional investment law, the weaknesses and strengths of the law and infrastructures, institutions and their effectiveness in coordinating the efforts to facilitate inflow of FDI to the region, are investigated. Finally, we emphasize the need for the KRG to further promote investment in infrastructure and to impact economic growth, which in turn reinforce each other by attracting more investment in infrastructure and the productive sectors.
Keywords: D53; 330; Financial market; foreign direct investment; FDI; government policy; Kurdistan; KRG; Direktinvestition; Ausländisch; Investitionspolitik; Standortpolitik; Kurdistan (Irak)